P2_4 A Very Light Balloon - Byrne, Jamie; Lewis, Elspeth; Dangerfield, Kyle; Walton, Sam (Physics Special Topics, 2017)
In this paper we have performed an experiment to verify whether the pressure inside a party balloon is equal to ambient atmospheric pressure, and then performed further calculation to find how powerful a light source would be needed to inflate a party balloon using radiation pressure alone. It was found that the pressure inside a balloon was within five percent of ambient atmospheric pressure, and that a light source of multiple terawatt light output would be needed to inflate a balloon, with a specific value of 8.9x10^12 W for it to inflate to a standard size.